Evaluation of strength and conditioning measures with game success in Division I collegiate volleyball: A retrospective study - Bunn, J. A.; Ryan, G. A.; Button, G. R.; Zhang, S. (The Journal of Strength and Conditioning Research, 2020)
The purpose of this study was to retrospectively assess relationships between strength and conditioning (SC) measures and game performance in Division I volleyball. Five years of SC and game data were collected from 1 women's Division I collegiate team, n = 76. Strength and conditioning measures included T-drill, 18.3 m sprint, back squat, hang clean, vertical jump, and broad jump. All game and SC stats were normalized to Z-scores. Analyses included assessing SC differences by position and multiple stepwise regression to assess relationships between game and SC stats. There was a significant difference by position for broad jump (p = 0.002), 18.3 m sprint (p = 0.036), vertical (p = 0.001), and total strength (p = 0.019). Overall, game performance and SC measures were significantly correlated (r = 0.439, p = 0.001). Multiple regression analyses indicated significant relationships (p = 0.05) between SC measures and game success by position as follows: defensive specialist stats with squat and total strength; setters game stats with hang cleans, T-drill, and broad jump; pin hitter game stats with vertical, squat, and total strength; middle blockers game stats with broad jump. These data indicate that SC measures correlate well with game performance and are specific by position. These data could help SC coaches create a more precise training approach to focus on improving specific measures by position, which could then translate to improved game performance. These data could also help coaches with talent identification to determine playing time and rotations to maximize player ability and achieve success.